SAT0290 HIGH SERUM MYOSTATIN LEVELS SUGGEST ACCELERATED MUSCLE SENESCENCE IN ACTIVE IDIOPATHIC INFLAMMATORY MYOSITIS. (2nd June 2020) - Anuja, A.; Singh, M.; Rai, M. K.; Singh, H.; Agarwal, V.; Gupta, L.
Abstract : Background: Inflammation is the forerunner to fibrosis and premature ageing in various systemic diseases. Hence it seems plausible that idiopathic inflammatory myopathies (IIM) may exhibit accelerated senescence too. Objectives: Hence we investigated the Myostatin: Follistatin system in the serum as a reflection of early senescence in myositis as compared with healthy and diseased controls. Methods: Patients with inflammatory myositis (ACR/EULAR criteria) presenting to the wards and outpatient clinic between December 2017 to August 2019 were recruited. Those with active infection, pregnancy, renal dysfunction or chronic kidney disease were excluded. Apart from patient and disease variables, activity and damage were assessed using standard IMACS score set measures. Patients in inception cohort were additionally followed up at 1 and 6 months. Myostatin and Follistatin were estimated in sera using ELISA (R&D systems, USA). Juvenile myositis and young adults (18-40 years) were subsequently analyzed separately. Non-parametric tests were used for paired and unpaired analysis. Results expressed as median. Results: 95 myositis (8 Juvenile myositis, 26 DM, 10 PM, 29 Overlap, 2 NAM 1 CAM and 19 ASS) patients (23 Male and 72 Female) with median age 38 (24.5-46.0) years and disease duration 0.9 (2.3-5.1) years were included. Serum Myostatin was lower in IIM than in healthy control (HC) (153.5 vs. 243.6 p<0.0001, Fig 1A ) but higher in IIM as compared with disease controls (153.5 vs 86.1 p=0.0174 Fig. 1B ). Serum myostatin was comparable between juvenile and adult myositis and in the various subsets of adult myositis (Fig. 1 C and D). Myostatin levels were higher in active as compared with inactive myositis in young adults (211.7 vs. 158.9, p=0.0149, Figure 1E ). Serum Myostatin correlated with height (r 0.3, p=0.003) and weight (r 0.2, p=0.047) but not MMT8 or muscle enzymes. Although Follistatin was lower in IIM than HC (198.4 vs 243.6, p=<0.0001), the neither Follistatin nor Myostatin: Follistatin ratios differ between subsets, and in active versus inactive disease Figure 2 A-D). On follow-up, the serial Myostatin estimation paralleled change in disease activity. Conclusion: Elevated serum Myostatin levels in active myositis raise the possibility of accelerated senescence in the inflamed muscle tissues which need further investigation. Acknowledgments: Partly funded by APLAR and IRA research grants awarded to LG. Disclosure of Interests: None declared